Obtaining and analysis of товассо, lettuce and rape plants transformed with human interferon alfa 2b gene - Gerasymenko, I.M.; Lypova, N.M.; Sakhno, L.A.; Shcherbak, N.L.; Sindarovska, Y.R.; Bannikova, M.A.; Sheludko, Y.V.; Kuchuk, N.V. (Фактори експериментальної еволюції організмів, 2009)
Plasmid constructs for Agrobacterium-mediated transformation of plant nuclear genome with human interferon alpha2b gene were built up and used to obtain transgenic plants of tobacco, lettuce and rape. Presence of the target gene was confirmed by PCR analysis and interferon activity in lettuce plants was shown by the vesicular stomatitis virus cytopathic effect assay.